Exploring the Meaning of Sense of Community among ‘Aisyiyah Cadres: A Phenomenological Study in A Faith based Women's Organization - Maryam, Effy Wardati; Rahayu, Yusti Probowati; Tondok, Marselius Sampe (Universitas Muhammadiyah Surakarta, 2025)
This study explores the meaning of sense of community among organizational cadres of 'Aisyiyah. Using a qualitative phenomenological approach, this study investigates the subjective experiences of two participants representing two types of cadres: natural cadres and instant cadres. Data were collected through in-depth semi-structured interviews and analyzed using reflexive thematic analysis. Six main themes emerged, reflecting cadres' sense of community in 'Aisyiyah: perceptions of the organization, organizational attachment, organizational involvement, adaptation and internalization of values, internal conflict, and drivers of involvement. The findings revealed that natural cadres whose experiences and values align with the organization demonstrated stable emotional engagement, coming from non-Association backgrounds experienced a more dynamic and complex engagement trajectory. This study advances understanding of how values, history, and social dynamics shape a sense of community in faith-based organizations such as 'Aisyiyah, a context that remains relatively underexplored in existing literature.